Effect of Adobe Flash CS6 Learning Media on Social Studies Learning Outcomes in Fifth Grade Student: Pengaruh Media Pembelajaran Adobe Flash CS6 terhadap Hasil Belajar IPS pada Siswa Kelas V SD - Romadhon, Muhammad Syahrul; Tirtoni , Feri (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to investigate the impact of using Adobe Flash CS6 learning media on social studies learning outcomes related to national events surrounding the proclamation of independence in fifth-grade students at SDN Keboananom. The research utilized a quantitative experiment with a Quasi Experimental research design in the form of a non-equivalent control group design. Data analysis involved the Independent Sample T-test to test the hypothesis and address the research problem. The results revealed a significant improvement in students' understanding of social studies concepts after using Adobe Flash interactive learning media, as indicated by the average posttest data exceeding the pretest data. The findings imply that the integration of Adobe Flash learning media in the material related to the proclamation of Indonesian independence positively impacted social studies learning outcomes in fifth-grade students, offering a potential solution for enhancing social studies education in elementary schools. Highlight: The study examines the impact of using Adobe Flash CS6 learning media on social studies learning outcomes in fifth-grade students. The research employs a quantitative experiment with a Quasi Experimental research design, utilizing a non-equivalent control group design. Data analysis involves the Independent Sample T-test to test the hypothesis and determine the effect of using Adobe Flash interactive learning media on understanding social studies concepts in SDN Keboananom. Keyword: Adobe Flash CS6, Learning Media, Social Studies, Learning Outcomes, Fifth-Grade Students.